Weak vs. Strong Ties: Explaining Early Settlement in WTO Disputes - Jiwon Lee; Teresa Wittgenstein (University of Hamburg, Institute of Law and Economics (ILE), 2017)
Empirical investigations of litigation at the WTO reveal a noteworthy pattern: the majority of disputes settle early, either during consultation, or prior to the issuance of a panel ruling. This is surprising, considering the structure of its remedial regime undermines the system's deterrent effect. It is, therefore, theorized that formal adjudication gains enforcement power by disseminating information on state conduct, unleashing reputational pressures. Building on the emerging stream of literature interested in the interaction between overlapping institutions, we contend that the degree to which defendants' are embedded in external trade agreements acts as an important determinant of dispute escalation at the WTO. The fear of reputational sanctions emanating from an adverse ruling exerts impetus for settlement in disputes involving defendants that are signatories of a few, shallow agreements. The “shadow of the future,” in the form of ongoing trade negotiations, heightens the sensitivity to reputation for states with a strong potential to increase market access in the future.To test our hypothesis we quantified evidence on settlement patterns for the organization's first fifteen years of operation. We have also compiled a novel dataset consisting of 233 trade agreements disputants were signatories to during our observation period. To account for diverse levels of integration, a measure of depth is included, applying the additive depth index introduced by the DESTA project. In order account for the fact that some provisions may be more relevant drivers of the depth of an agreement, we conducted a factor analysis to unravel unobserved, latent variable(s). We find strong support for the claim defendants' wider integration in the trade realm predicts settlement dynamics within the WTO dispute settlement system. Our results remain statistically significant despite alternative specifications and robustness tests.
Keywords: 330